Outcomes of diabetic patients with end-stage heart failure listed for heart transplantation: a propensity-matched analysis. (14th October 2021) - Akintoye, E; Alvarez, P; Briasoulis, A
Abstract: Background: There are on-going concerns about offering heart transplants to patients with diabetes due to the risk of poor outcomes. We investigated the current trends and outcomes of patients listed for heart transplants in the U.S. and provided a method for risk-stratification. Methods: Using data from the United Network for Organ Sharing (UNOS), we identified heart failure patients listed for heart transplants between 2010 and 2019. Diabetic patients were propensity-matched with non-diabetes, and waitlist mortality as well as post-transplant graft survival were compared between the two matched groups. Further risk-stratification of the diabetic cohort was done based on the risk factors that independently predict the risk of graft failure. Results: 28, 928 adult patients (30% diabetic) with end-stage heart failure were added to the waitlist over the study period. In the propensity-matched cohort, waitlist mortality was higher with diabetics compared to non-diabetics: 19.3 vs 17.1 deaths per 100 person-years, respectively, (HR=1.13 (95% CI=1.04–1.22, p=0.002). Over the study period, 5739 diabetics (mean age 57.6 years, 21.9% female) were transplanted. A total of 1308 (23.3%) and 1143 (20.4%) graft failures occurred in diabetic and non-diabetic recipients, respectively. Compared to non-diabetics, diabetics experienced worse graft survival (HR=1.17, 95% CI=1.08–1.26, p<0.001). We developed a risk score based on the 12 risk factors/markers that independently predict worse graft survival and a risk score of 4 reasonably differentiates between low and high-risk diabetics. Low risk diabetics (score≤4) had similar graft survival as non-diabetics with 1- and 5-year survival of 92.7% and 80.5%, respectively, (HR=0.91, 95% CI=0.82–1.01, p=0.06). On the other hand, high-risk diabetics had worse graft survival compared to non-diabetics (HR=1.52, 95% CI=1.38–1.67, P<0.001) with 1- and 5-year graft survival of 86.8% and 69.8%, respectively. Conclusion: Diabetic patients with end-stage heart failure listed for heart transplantation experience higher waitlist mortality and worse post-transplant graft survival compared to non-diabetics. However, a simple risk score can be used for further risk-stratification in these patients to maximize survival benefit. Funding Acknowledgement: Type of funding sources: None.